If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + w)(4w + -1) = 0 Reorder the terms: (6 + w)(-1 + 4w) = 0 Multiply (6 + w) * (-1 + 4w) (6(-1 + 4w) + w(-1 + 4w)) = 0 ((-1 * 6 + 4w * 6) + w(-1 + 4w)) = 0 ((-6 + 24w) + w(-1 + 4w)) = 0 (-6 + 24w + (-1 * w + 4w * w)) = 0 (-6 + 24w + (-1w + 4w2)) = 0 Combine like terms: 24w + -1w = 23w (-6 + 23w + 4w2) = 0 Solving -6 + 23w + 4w2 = 0 Solving for variable 'w'. Factor a trinomial. (-6 + -1w)(1 + -4w) = 0Subproblem 1
Set the factor '(-6 + -1w)' equal to zero and attempt to solve: Simplifying -6 + -1w = 0 Solving -6 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1w = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1w = 0 + 6 -1w = 0 + 6 Combine like terms: 0 + 6 = 6 -1w = 6 Divide each side by '-1'. w = -6 Simplifying w = -6Subproblem 2
Set the factor '(1 + -4w)' equal to zero and attempt to solve: Simplifying 1 + -4w = 0 Solving 1 + -4w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4w = 0 + -1 -4w = 0 + -1 Combine like terms: 0 + -1 = -1 -4w = -1 Divide each side by '-4'. w = 0.25 Simplifying w = 0.25Solution
w = {-6, 0.25}
| 1/2×10h=35 | | s^2+3s=-16 | | 5x+7=12x+35 | | 6x-7/5x=3 | | 8x-10=8x-10 | | 13x-9=8x-34 | | x^2+6x = 0 | | 7b+7=42 | | 10x-12=4x+48 | | 11x+12=10x+18 | | 2x(5+3)-16= | | 3p/5=9/4 | | 2x(5+3)-4= | | 3/4-x=7 | | p=2*66+2*94 | | 6x^2*2x^2= | | i+-56=-82 | | 5x/14-11x/7= | | 2.5x=85 | | -16x^2+14t+2=0 | | k-13=-5 | | u-14=-46 | | 3s-2t/6*12/9s-3t | | h(x)=x(x+2)-x(2x-1) | | 50/x=.47 | | y+(-10)=-8 | | 2x-8/7x=1 | | 18-4k=-10+10k | | z=8-i | | 22+3x=-2-8x | | 2x-7/2=3 | | 5a-20+a*-3=50 |